The Maria asteroid family - Aljbaae, S. [UNESP] (2017)
The Maria asteroid family is a group of S-type asteroids. Its location adjacent to the left side of the 3J:-1A mean-motion resonances could be the reason for the absence of the left side of the 'V' shape in the (a, 1/D) domain. This family can be considered as a likely source of ordinary chondrite-like material. In this work, we make use of the time dependence of the asymmetric coefficient AS describing the degree of asymmetry of the C distribution of a fictitious Maria family generated with the value of the ejection velocity parameter VEJ = 35ms-1 to obtain an age estimate of 1750 +537 -231 Myr, in good agreement with the family age found in the literature. Analysing the contribution to the near-Earth object (NEO) population, we found that about 7.6 per cent of presently known near-Earth asteroids (NEAs) have orbits similar to asteroids from the Maria family. Only ~1.7 per cent of our simulated family can stay in NEO space for more than 10 Myr, while only five asteroids become NEOs in the last 500 Myr of the simulation.